Assessment and management of secondary bacterial infections complicating Mpox (Monkeypox) using a telemedicine service. A prospective cohort study. (June 2023) - Moody, Samuel; Lamb, Thomas; Jackson, Eleri; Beech, Alison; Malik, Nabihah; Johnson, Leann; Jacobs, Nathan
Introduction: During spring 2022, an outbreak of Monkeypox (mpox) emerged as an infection of concern in Europe. Due to the overlapping clinical features of mpox and bacterial infections, diagnosis of concomitant bacterial infection is challenging. In this prospective cohort study, we report the incidence, severity, and progression of patients with secondary bacterial infection complicating mpox infection. Method: Data were collected via a bespoke mpox telemedicine service provided by Infection services at North Manchester General Hospital, UK. A diagnosis of secondary bacterial infection was based on the history (balanitis, surrounding erythema, purulent discharge and nasal ulceration) and review of patient-collected medical photography. Patient were reviewed face-to-face where necessary. Results: Secondary bacterial infection was diagnosed in 15 of 129 (11.6%) patients with mpox. Three patients with secondary bacterial infection (3/129, 2.3%) required admission to hospital and one patient underwent surgical debridement. Median healing (thus, isolation) times were longer in those with bacterial infection. Discussion: In this prospective cohort study of patients with mpox, secondary bacterial infection was infrequent and predominantly mild. The virtual ward and telemedicine follow up allowed for the prompt recognition of secondary bacterial infections and timely antibiotic administration. Due to concerns regarding nosocomial transmission, mild clinical course and limited inpatient bed capacity, we believe this model of outpatient management for mpox (Clade II B.1 lineage) could be replicated in other low risk populations where suitable home isolation facilities exist.